Die Fakten in den Naturwissenschaften: Zur Zukunft der Wissenschaftsgeschichte - Osten, Philipp (Berichte zur Wissenschaftsgeschichte, 2018)
The Facts in the case of science. The article casts an eye on the role of scientific facts in relation to the circumstances, under which they emerge, and discusses the challenges for a history of science in a near future. The author assumes that science, the economy, ideologies, and religious belief will keep influencing each other. He recommends an open mind for new sources and pleads for interdisciplinary approaches.
Gesehen am 05.05.2021